A Rational Threshold Signature Model and Protocol Based on Different Permissions. (23rd July 2014) - Wang, Bojun; Cai, Cheng; Zhou, Quan
Abstract : This paper develops a novel model and protocol used in some specific scenarios, in which the participants of multiple groups with different permissions can finish the signature together. We apply the secret sharing scheme based on difference equation to the private key distribution phase and secret reconstruction phrase of our threshold signature scheme. In addition, our scheme can achieve the signature success because of the punishment strategy of the repeated rational secret sharing. Besides, the bit commitment and verification method used to detect players' cheating behavior acts as a contributing factor to prevent the internal fraud. Using bit commitments, verifiable parameters, and time sequences, this paper constructs a dynamic game model, which has the features of threshold signature management with different permissions, cheat proof, and forward security.